Collaborating across cultures: Cultural metacognition and affect-based trust in creative collaboration - CHUA, Roy Y. J. (Institutional Knowledge at Singapore Management University, 2012)
We propose that managers adept at thinking about their cultural assumptions (cultural metacognition) are more likely than others to develop affect-based trust in their relationships with people from different cultures, enabling creative collaboration. Study 1, a multi-rater assessment of managerial performance, found that managers higher in metacognitive cultural intelligence (CQ) were rated as more effective in intercultural creative collaboration by managers from other cultures. Study 2, a social network survey, found that managers lower in metacognitive CQ engaged in less sharing of new ideas in their intercultural ties but not intracultural ties. Study 3 required participants to work collaboratively with a non-acquaintance from another culture and found that higher metacognitive CQ engendered greater idea sharing and creative performance, so long as they were allowed a personal conversation prior to the task. The effects of metacognitive CQ in enhancing creative collaboration were mediated by affect-based trust in Studies 2 and 3.